Integrasi Pembelajaran Matematika dan Nilai-Nilai Akidah Akhlak dalam Meningkatkan Karakter Religius Peserta Didik di MTs Miftahul Ishlah Tembelok - Habiburrahman , Muhammad; Suriyandi, Lalu; Husaini, Muhammad Lutfiyan Fakhril (Mandalika Mathematics and Educations Journal, 2025)
This research is a qualitative descriptive field research. Data collection used observation, interviews, and documentation techniques. Data processing involved data reduction, data display, and conclusion drawing. The results of this study indicate: first, not all Mathematics teachers have implemented the integration of Mathematics and moral beliefs in understanding the oneness of God through the concept of natural number sequences. This is because teachers have difficulty explaining the connection between the concept of natural number sequences and the concept of the oneness of God. Teachers have tended to explain the material purely in Mathematics without integrating it with the concept of the oneness of God. Second, not all Mathematics teachers have implemented the integration of Mathematics and moral beliefs in understanding human existence in the world through the concept of geometry. This is because teachers are not yet accustomed to linking geometric concepts with human existence in the world. Third, not all Mathematics teachers have implemented the integration of Mathematics and moral beliefs in understanding the attitude of surrender to God through the concept of fractional number sequences. This is because teachers lack adequate knowledge about the attitude of surrender to God that will be integrated with the concept of fractional number sequences. Fourth, the integration of mathematics and moral values in understanding the concepts of honesty, accuracy, and simplicity through multiplication has not been implemented by all mathematics teachers. This is because teachers have difficulty explaining the connection or relationship between the concept of multiplication and honesty, accuracy, and simplicity.